PENGARUH KOMPENSASI TERHADAP LOYALITAS GURU DI SMPIT AL LAUZAH TANGERANG SELATAN - Sumayyah Afifah; Taufiqurrahman Taufiqurrahman (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the effect of compensation on teacher loyalty at SMPIT Al lauzah. The method used is quantitative. The population in this study were all 30 teachers at SMPIT Al Lauzah. The analytical tools used in this study are simple linear regression, the coefficient of determination, and the t test. Data processing uses SPSS 21 statistics for windows. Based on the research results it is known that simultaneously compensation has a significant and positive effect on teacher loyalty, that there is a compensation effect on student teacher loyalty at SMPIT Al Lauzah of 23.1%. And the situation with the regression coefficient of the variable X of 1.417 means that for each increase in compensation by one unit, it will lead to an increase in loyalty by 1.417.